A site-specific DNA methylation biosensor for both visual and magnetic determination based on lateral flow assay. Issue 7 (18th February 2021) - Zhang, Jiaxing; Liu, Xiaonan; Zhang, Sinong; Cai, Yu; Ma, Kang; Hua, Kai; Cui, Yali
Abstract : Optical and magnetic signals facilitate the result interpretation and 0.1% target variant can be distinguished within 90 min from sequence discrepancy. Abstract : Tumorigenesis driven by abnormal DNA methylation has highlighted the need to develop a portable, rapid and sensitive strategy for accurate methylation detection with a specific cancer-prognostic gene, which caters to the popularization of precision medicine. In this study, a site-specific biosensor for both visual and magnetic DNA methylation determination has been established based on lateral flow assay. By introducing digoxin- and biotin-labeled primers into PCR, the amplicons can be recognized and captured by gold magnetic nanoparticles (GMNPs) in this biosensor. Working as a signal probe, the optical property of GMNPs allows the amplicons to be interpreted with naked eyes avoiding any complex equipment and cumbersome operation after PCR. Moreover, by virtue of the magnetic property of GMNP, the signal can be explained and recorded by a magnetometer in clinical practice. The introduction of tailor-made primer sets makes it possible to accurately distinguish 0.1% methylated variants in the presence of numerous unmethylated variants as strong interferential background and vice versa at target cytosine–guanine dinucleotide. A distinct signal can be observed with as low as 0.01 pg variants for both visual and magnetic analyses. As a significant tumor suppressor gene, the promoter methylation status of miR-34a is accurately determined with not only cell lines but also with clinical samples, which demonstrates the great potential of this biosensor for cancer diagnosis and prognosis.